2021
DOI: 10.36103/ijas.v52i5.1448
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Studty on Growth, Carcass Traits and Body Composition of Awassi and Karadi Lambs Raised Under Two Levels of Feeding and Slaughtered at Different Weights: 1- Growth Performance and Carcass Traits

Abstract: Sixteen weaned (3.5-4 months) entire male lambs from each of Awassi and Karadi were weighed and randomly divided equally into two groups to receive concentrate (16% crude protein and 2769 kcal energy) either ad libitum or 3% of their body weights, and to be slaughtered at 36 or 44 kg. Results revealed that overall means of daily gain in weight, dressing percentage based on slaughter and empty body weight, rib eye area and fat thickness were 0.258±0.01 kg, 46.54± 0.49%, 54.35 ± 0.40%, 14.98 ±0.44 cm2 and 2.86 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
3
1
1
Order By: Relevance
“…It is generally agreed that daily live weight gain in lambs slaughtered at different weight decrease with increasing slaughter weight (2,44,50), mainly due to fat deposition. However, this result agree with the finding of Balci and Karkas (12) and Al-Sherwany and Alkass (10) who noticed an increase in average daily gain with the increasing slaughter weight of lambs. Fattening period for docked and undocked lambs being 49.67 and 37.83 days, respectively and the difference was not significant (Table 1).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…It is generally agreed that daily live weight gain in lambs slaughtered at different weight decrease with increasing slaughter weight (2,44,50), mainly due to fat deposition. However, this result agree with the finding of Balci and Karkas (12) and Al-Sherwany and Alkass (10) who noticed an increase in average daily gain with the increasing slaughter weight of lambs. Fattening period for docked and undocked lambs being 49.67 and 37.83 days, respectively and the difference was not significant (Table 1).…”
Section: Resultssupporting
confidence: 92%
“…It is of interest to note that no statistical analysis was carried out for this trait because of lambs are fed on a group basis. Moreover, the feed conversion ratio obtained in the current work is lower than those reported earlier for Karadi and Awassi lambs by Alkass and Kak, (9), Alkass and Hassan (6) and Al-Sherwany and Alkass (10). 2).…”
Section: Resultscontrasting
confidence: 88%
See 2 more Smart Citations
“…Carcass composition: The weights in kg of lean, fat and bone in the left side of the carcass increased linearly as the slaughter weight increased in the docked and intact lambs (Tables 1 , 2). This result were close to other workers (5,7,11,30), who reported that as the carcass weight increased, the weights of lean, fat and bone increased. The allometric growth coefficients of dissectible lean and bone weights in docked and intact Karadi lambs were negative heterogenic (b<1), indicating low impetus and early maturing tissue, and the growth of these two tissues are significantly (P<0.01) slower than carcass weight.…”
Section: Resultssupporting
confidence: 91%